The Use Of Zakat Logo In Optimizing The Collection Of Corporate Zakat In The State Of Kedah - Azman Ab Rahman; Afaf Sukari; Setiyawan Gunardi; Syed Mohd Najib Syed Omar (USIM PRESS, 2024)
VOL. 28 NO. 1 (2023): JANUARY ISSUE Page(58-68)